Pengembangan Aplikasi Berbasis Desktop Penjualan Rumah dengan Metode Waterffal - Muhammad Kharisma Ade Miharja; Muhammad Riyadhi Al Fikri; Esra Tarigan; Aka Suwarno; Sri Mulyati; Yulianti Yulianti (Teknik Informatika Universitas Pamulang, 2022)
Todays information systems are particularly conducive to the daily needs and convenience of the community, in todays modern age so much of the activities that could be made easier by the help of the application information system, for example to the customer customer no longer need to take the time to come to see and select the type of products sold by property providers, Therefore the researcher wants to create a desktop based application program through quick research to make sales transactions and purchases easier in the property sector, in which case researchers want to create a desktop home sales application. In the application there are multiple functions that begin with customer record-keeping, customer data storage and display products sold by property providers. To achieve the design of the application, researchers use more like waterfall development software methods, the research phase will be starting through software analysis and requirements, application design interface, implementation, and then final stage will be where the application is tested. At the testing stage all is as we would like it to be, the applications are functioning accordingly, and it is hoped that they will be useful in supporting communities in property sector transactions.